Experimental Investigation of the Thermal Expansion Characteristics of Anthracite Coal Induced by Gas Adsorption. (22nd February 2023) - Wang, Ran; Su, Xianbo; Yu, Shiyao; Su, Linan; Hou, Jie; Wang, Qian
Abstract : The coal matrix can expand after gas adsorption, thus reducing the permeability of coal reservoirs and further affecting the coalbed methane production. Whether the heat released by coal adsorbing gas is a cause of the coal expansion has not yet been determined. Therefore, the anthracite coal with high gas adsorption capacity was used; under the conditions of 35°C and 1-6 MPa, the adsorption capacity and the adsorption heat of coal adsorbing CO2 and CH4 were tested. The specific heat capacity and thermal expansion coefficient of coal at 35°C were tested. The temperature change of the coal after being heated was calculated by combining the absorption heat and specific heat capacity; also, the thermal expansion rate was calculated by combining the temperature change and expansion coefficient. In addition, the cube law was used to calculate the permeability change of coal before and after the adsorption expansion. The results show that the changes in the gas adsorption capacity and adsorption heat of the coal obey the Langmuir equation, and those to CO2 are both higher than to CH4 . The temperature of coal increases after the heat is released in the process of CO2 and CH4 adsorption, and the temperature change of coal adsorbing CO2 and CH4 reaches 102°C and 72°C, respectively, at 6 MPa. The thermal expansion rate of coal adsorbing CO2 and CH4 reaches 5.40% and 3.81%, at 6 MPa, respectively. It is found that a higher gas pressure could lead to a higher temperature change, a higher thermal expansion rate, as well as a higher thermal expansion and coal deformation. After the adsorption of CO2 and CH4, the coal permeability is reduced by 20.43% and 14.66%, respectively, at 6 MPa. Both the thermal expansion rate and the permeability change with the gas adsorption pressure obey the Langmuir equation. Therefore, the adsorption expansion of coal may be thermal expansion caused by the heat released by coal adsorbing gas.